Intranasal delivery of a chimpanzee adenovirus vector expressing a pre-fusion spike (BV-AdCoV-1) protects golden Syrian hamsters against SARS-CoV-2 infection - Wang, Shen; Xu, Long; Mu, Ting; Qin, Mian; Zhao, Ping; Xie, Liang; Du, Linsen; Wu, Yue; Legrand, Nicolas; Mouchain, Karine; Fichet, Guillaume; Liu, Yi; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
We evaluated the immunogenicity and protective ability of a chimpanzee replication-deficient adenovirus vectored COVID-19 vaccine (BV-AdCoV-1) expressing a stabilized pre-fusion SARS-CoV-2 spike glycoprotein in golden Syrian hamsters. Intranasal administration of BV-AdCoV-1 elicited strong humoral and cellular immunity in the animals. Furthermore, vaccination prevented weight loss, reduced SARS-CoV-2 infectious virus titers in the lungs as well as lung pathology and provided protection against SARS-CoV-2 live challenge. In addition, there was no vaccine-induced enhanced disease nor immunopathological exacerbation in BV-AdCoV-1-vaccinated animals. Furthermore, the vaccine induced cross-neutralizing antibody responses against the ancestral strain and the B.1.617.2, Omicron(BA.1), Omicron(BA.2.75) and Omicron(BA.4/5) variants of concern. These results demonstrate that BV-AdCoV-1 is potentially a promising candidate vaccine to prevent SARS-CoV-2 infection, and to curtail pandemic spread in humans.